Occasional Tillage in a Wheat-Sorghum-Fallow Rotation - A. Schlegel; J. D. Holman (Kansas Agricultural Experiment Station Research Reports, 2018)
Beginning in 2012, research was conducted in Garden City and Tribune, KS, to determine the effect of a single tillage operation every 3 years on grain yields in a wheat-sorghum-fallow (WSF) rotation. Grain yields of wheat and grain sorghum were not affected by a single tillage operation every 3 years in a WSF rotation. Grain yield varied greatly by year from 2014 to 2017. Wheat yields ranged across years from mid-20s to 80 bu/a at Tribune and about 10 (hail damage) to near 60 bu/a at Garden City. Grain sorghum yields ranged from less than 60 to greater than 140 bu/a, depending upon year and location. In no year or location, were grain yields significantly affected by a single tillage operation. This indicates that if a single tillage operation is needed to control troublesome weeds, that grain yields will not be significantly affected. Furthermore, if weed populations were high enough to cause yield reductions, then tillage might improve yields.
Keywords: wheat-sorghum-fallow rotation; occasional tillage in rotations; tillage; southwest Kansas